Video game play as nightmare protection: a preliminary inquiry with military gamers - Gackenbach, Jayne; Ellerman, Evelyn; Hall, Christie (My University, 2011)
Soldiers who play video games to varying degrees were solicited to fill out a survey on dreams and gaming. A prescreening filtered out those who were not soldiers, who did not game and who were suffering from various psychological problems in the last six months. The remaining soldiers filled out these inventories; general and military demographics, history of video game play, Emotional Reactivity and Numbing Scale (ERNS), and a Trauma Inventory. They were then asked to provide two dreams, one recent and one that was impactful from their military service. Following the military dream they filled out Impactful Dreams Questionnaire (IDQ) about that dream only. Dream content analysis was conducted using threat simulation, war content and lucid/control/gaming content. High and low end frequency gamer groups were identified and compared on these dream content scales. Because the nightmare literature shows that affect load and distress are predictors of nightmare suffering. ERNS and Trauma history were covariates in the ANCOVA’s on gamer group x dream type. It was found that the high end gaming group exhibited less threat and war content in their military dreams than the low end group.
Keywords: nightmares; video games; threat simulation; military; war; dreams